A nanobody toolbox to investigate localisation and dynamics of Drosophila titins and other key sarcomeric proteins - Vincent Loreau; Renate Rees; Eunice HoYee Chan; Waltraud Taxer; Kathrin Gregor; Bianka Mußil; Christophe Pitaval; Nuno Miguel Luis; Pierre Mangeol; Frank Schnorrer; Dirk Görlich (eLife, 2023)
Measuring the positions and dynamics of proteins in intact tissues or whole animals is key to understanding protein function. However, to date, this is challenging, as the accessibility of large antibodies to dense tissues is often limited, and fluorescent proteins inserted close to a domain of interest may affect protein function. These complications apply in particular to muscle sarcomeres, arguably one of the most protein-dense assemblies in nature, which complicates studying sarcomere morphogenesis at molecular resolution. Here, we introduce a toolbox of nanobodies recognising various domains of the two Drosophila titin homologs, Sallimus and Projectin, as well as the key sarcomeric proteins Obscurin, α-Actinin, and Zasp52. We verified the superior labelling qualities of our nanobodies in muscle tissue as compared to antibodies. By applying our toolbox to larval muscles, we found a gigantic Sallimus isoform stretching more than 2 µm to bridge the sarcomeric I-band, while Projectin covers almost the entire myosin filaments in a polar orientation. Transgenic expression of tagged nanobodies confirmed their high affinity-binding without affecting target protein function. Finally, adding a degradation signal to anti-Sallimus nanobodies suggested that it is difficult to fully degrade Sallimus in mature sarcomeres; however, expression of these nanobodies caused developmental lethality. These results may inspire the generation of similar toolboxes for other large protein complexes in Drosophila or mammals.